Kajian Penyebaran dan Marginalisasi Tari Gandang Lasuang - Raudhatul Fadillah; Indrayuda Indrayuda (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Gandang Lasuang Dance is a traditional dance art that developed in batang tajongkek, precisely in Aua Sarumpun studio. In this dance, the properties are Lasuang, pestle, katidiang. This dance tells the story of how a farmer pounded rice using lasuang, where the rice to be pounded would become rice. In addition, this dance is also accompanied by music such as Talempong, Gandang dol, sleigh-giring. The purpose of this study is to analyze and describe the spread of Gandang Lasuang Dance and the factors causing the marginalization of Gandang Lasuang Dance. This research method uses qualitative research. The location of the research was conducted in Sanggar Aua Sarumpun, Batang Tajongkek Village, South Pariaman, Pariaman City. The results showed that the Study of the Spread and Marginalization of Gandang Lasuang Dance in Batang Tajongkek was quite well developed. Judging from its use, this art was previously only used as a medium for self-entertainment when pounding rice, but now it has been used as entertainment for the people of Batang Tajongkek Village, besides that the Gandang Lasung Dance is also performed in various art events such as PKK events, and bundo kanduang events and so on.